“In 3 Years We Would Have Solved This”: Jokowi, ASEAN And Transboundary Haze - Helena Varkkey (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2017)
Joko Widodo took up office as President of Indonesia barely a month after the Republic ratified the ASEAN Agreement on Transboundary Haze Pollution. This momentous ratification coupled with the severe haze during his first few months in office, positioned haze as a priority issue for Jokowi and his administration. Since then, Jokowi has been proactively taking action at both the central and local levels. This was hoped to be a stepping stone towards better cooperation at the regional level. However, this was met with a somewhat contradictory state- ment by Jokowi in 2015 that quite firmly requested the ASEAN region to give him ‘three years’ to solve the haze issue. This could be taken to mean that Indo- nesia wanted to be ‘left alone’ to deal with fire and haze issues for three years without ASEAN ‘interference’. It is important to also assess this administration’s style of engagement with the ASEAN organization and neighbouring countries over haze issues, particularly Malaysia and Singapore. A thorough consideration of these factors would be able to provide a detailed assessment of the Jokowi administration’s attitude towards ASEAN cooperation over haze, and what this means for the broader ASEAN community.